Kontribusi Hadis Dalam Tafsir Kontekstual Terhadap Isu Kontemporer HAM, Menjaga Lingkungan, dan Keadilan Sosial - Abdul Aziz; Uswatun Hasanah (Indo Publishing, 2025)
This study aims to determine the contribution of the Hadith in contextual interpretation to contemporary issues of human rights, environmental protection, and social justice. Overall, the contribution of the Hadith to the interpretation of human rights issues in Islam lies in explaining, reinforcing, and operationalizing the principles of the Quran, so that humanitarian values ​​are not merely conceptualized at a level, but are embodied in the social practices of the Prophet Muhammad (peace be upon him), which were violent and upheld respect for human dignity. The Hadith also establishes a normative structure for human rights by establishing legal boundaries that safeguard the right to life while considering justice and social welfare. It also expands the meaning of human rights beyond mere physical protection to a moral obligation to help one another, maintain honor, and meet the needs of others. Thus, the Hadith is key to understanding and implementing human rights in Islam in a comprehensive, holistic, and contextual manner, in accordance with the mission of rahmatan lil-'alamin (blessing for all the worlds).